Reconstructions of eyelid defects - Nirmala Subramanian (Indian Journal of Plastic Surgery)
Eyelids are the protective mechanism of the eyes. The upper and lower eyelids have been formed for their specific functions by Nature. The eyelid defects are encountered in congenital anomalies, trauma, and postexcision for neoplasm. The reconstructions should be based on both functional and cosmetic aspects. The knowledge of the basic anatomy of the lids is a must. There are different techniques for reconstructing the upper eyelid, lower eyelid, and medial and lateral canthal areas. Many a times, the defects involve more than one area. For the reconstruction of the lid, the lining should be similar to the conjunctiva, a cover by skin and the middle layer to give firmness and support. It is important to understand the availability of various tissues for reconstruction. One layer should have the vascularity to support the other layer which can be a graft. A proper plan and execution of it is very important.